Dramatic Function of Soundtrack Film Message Model: Analytical Study - Qays Oudah Qasim (Basrah Arts Journal, 2024)
The soundtrack was characterized by a dramatic function that played an essential role in building the cinematic and dramatic landscape and centered on how to support and support the event and film scene with multiple and varied functions in the (message film) film and emphasize the foundations on which the soundtrack served as a fundamental dramatic function in the artistic content and film event. Chapter I included the methodological framework in which the research problem of research arose after the researcher conducted a field survey of some films in which the soundtrack had a dramatic function that played a key role in the construction of the film scene. In this sense, the researcher seeks to raise the question of what is the dramatic function of the soundtrack in the film message? Hence the importance of research from which we mention1:- Highlight the elements of the soundtrack and its relationship to the film's scene event Then the goal of the research centered on the dramatic function of the soundtrack in the film and the research is determined by the music of the film. E-The first chapter of the chapter came with researchers who specialized the first elements and components of the soundtrack I only the second was entitled the dramatic effect of the soundtrack musician Then the theoretical framework was marked and then chapter III was followed by research procedures and analysis of the soundtrack models of the music of the message film.